Blocking plasma cell fate enhances antigen-specific presentation by B cells to boost anti-tumor immunity - Yunqiao Li; Raag Bhargava; Jenny Tuyet Tran; Tanya R. Blane; Linghang Peng; Fangkun Luan; Zhe Huang; Zefan Zhang; Yunfan Sun; Changchun Xiao; David Nemazee (Nature Communications)
Abstract B cells engage in anti-tumor immunity but how they contribute to cancer suppression remains unclear. We report that inhibiting plasma cell differentiation either in IgMi mice lacking Igh elements needed for antibody secretion or in mice with B cell-specific knockout of Blimp-1 (Blimp-1 BcKO) promotes rather than inhibits antitumor immunity and increases numbers of activated B cells. Deficiency of Blimp-1 in tumor-infiltrating B cells generates a unique transcription profile associated with expansion of mutated clones targeting cognate tumor cells. Major histocompatibility complex class II (MHC II) is required for anti-tumor efficacy. Blimp-1-deficient B cells have increased expression of CD80 and CD86 costimulatory molecules that enhance effector T cell function. The Blimp-1 inhibitor valproic acid suppresses tumor growth in a B cell-dependent manner. Thus, inhibition of plasma cell differentiation results in enhanced tumor-specific antigen presentation by B cells and thereby tumor repression, suggesting a potential avenue of immunotherapy against cancer.